PARTNERTRALISTIC SUPERVISION APPROACH TO IMPROVING THE QUALITY OF BASIC EDUCATION - Ahmad Sulhan; Mohammad Viktor Farid Hakim (AL-ISHLAH: Jurnal Pendidikan, 2020)
The research objective was to obtain a partnership concept in the supervision activities at SDIT Anak Sholeh Mataram in order to improve the quality of education. Basically, supervision activities are not only routine evaluations of educational activities. The research method used qualitative with case studies. Data collection techniques used observation, interviews, and documentation. The data analysis technique consists of three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that a partnertralistic form of supervision at SDIT Anak Sholeh Mataram was evident from the involvement of parents, teachers, school principals, school committees, and class forums in various educational activities. This has implications for developing intense communication with all parties in increasing educational activities in schools.